Impact of the Covid-19 pandemic on the relationship between financial performance and the ESG of Brazilian publicly traded companies - Douglas Laurindo da Silva; Renato Henrique Gurgel Mota; Angelica Maria Constantino de Moura (Revista Ambiente Contábil)
Purpose: To analyze the impact of the Covid-19 Pandemic on the relationship between ESG (Environmental, Social and Governance) scores and the financial performance of Brazilian publicly traded companies.